ANIMO MASYARAKAT DALAM MENGIKUTI KEGIATAN MAJELIS TA'LIM DI NAGARI TALUNAN MAJU, KECAMATAN SANGIR BALAI JANGGO, KABUPATEN SOLOK SELATAN - Ai Nuraini; Alimir Alimir (KOLONI, 2022)
The background of the problems found, they do not want to attend the ta'lim assemblies but instead chat with each other, weather conditions, busy selling, busy with their respective jobs both housewife work, taking care of children or going to the garden. This shows that there is still a lack of public interest in participating in the activities of the ta'lim assembly. Therefore, the authors are interested in researching what are the causes of the low public interest in participating in the activities of the ta'lim assembly in Jorong Talunan Baru I. This type of research uses descriptive qualitative research methods and is in the form of field research. With key informants, namely the community and supporting informants, namely administrators, congregations and parties who directly know about the activities of the ta'lim assembly. To collect data, the authors conducted observations, interviews and documentation. After the data is collected, data processing and analysis is carried out. Furthermore, the technique of guaranteeing the validity of the data is carried out by means of data triangulation. Based on the results of the author's research, that the causes of the low interest of the community in participating in the activities of the ta'lim assembly include unfriendly weather conditions, having a baby and getting old sick, being busy as a farmer and selling, sudden work and external affairs, there is no will of heart, coming obstacles, long distances, and suddenly heavy rain, muddy roads, difficult vehicles and some still showing off clothes and decorations. So it can be concluded that the cause of the low public interest in Jorong Talunan Baru I, Nagari Talunan Maju, Sangir Balai Janggo District, South Solok Regency is still low. Keywords: Enthusiasm, community, ta'lim assembly